Awareness and Compliance in the Civil Registration of Residents in a Municipality of Negros Occidental - Jeremy G. Celeste; Romeo R. Tinagan (Philippine Social Science Journal, 2020)
Civil registration is a continuous procedure, which aims to establish permanent records of individual vital events from the day it was born to the day it dies. Every country has its compulsory and universal recording process of important events about their population. Civil registration intends to institute a citizen’s legal documents and form primary sources of vital statistics.  The Philippines is governed by Act No. 3753 or the Civil Registry Law, which mandates that all vital events should be registered. Timely registration of vital events such as birth, marriage, and death is very important and crucial. Hence, this study assessed residents’ awareness of and compliance with civil registration of vital events. Also, it explored the challenges encountered by residents in the registration of vital events mandated by law.